KEBIJAKAN SOSIAL UMAR BIN KHATTAB : MEMBANGUN KEADILAN BAGI KAUM LEMAH - Sofia Fahrany; Daud Rasyid; Haliza Adelia (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2026)
Abstract.This study analyzes the social policy of Umar bin Khattab as the second caliph in the Khulafā’ al-Rāsyidīn. For the research method using qualitative descriptive, namely literature study, biography of Umar bin Khattab, fiqh economy Umar Bin Khattab, scientific journals with a historical-normative approach to answer the formulation of the problem, namely: 1. How is Umar bin Khattab's social policy, 2. Building justice for the weak, 3. Protection of vulnerable groups as the foundation of his leadership. The results of the study show that Umar succeeded in building an inclusive social system through Baitul Māl, social security, minority protection, administrative reform, and economic policies oriented towards public welfare. Umar's social leadership model is very relevant as a reference in designing contemporary public policies, it should be obeyed as Allah SWT says in Surah An-Nisa verse 59 which reads: